Level of service of public transport operation - pilot study - Markéta Jirmanová; Vojtěch Novotný; Nikol Dousková (Acta Polytechnica CTU Proceedings)
Smart transport planning based on the use of available data while supporting sustainable transport modes is an integral part of the Smart city concept. This article presents a critical analysis of the Level of Service of Public Transport Operation Assessment Method, which is based on two indicators - the reliability index and the travel speed index. The method is applied to a larger sample of data from several different cities, it makes it possible to evaluate the possible shortcomings of the method, since the method has not yet been applied to such a large number of case studies.